Retrieval of a broken dental needle close to the facial artery after cervical migration - De Queiroz, Sormani Bento Fernandes; De Lima, Valthierre Nunes [UNESP]; Holanda Amorim, Pedro Henrique Gonçalves; Magro-Filho, Osvaldo [UNESP]; Amorim, Rivadavio Fernandes Batista (Wolters Kluwer, 2016)
Use of imaging tools like digital C-arm, tridimensional tomography, and navigational surgery has proven its value to the surgical removal of broken needles. A 32-year-old patient was referred for evaluation of a fractured needle during inferior alveolar nerve block attempt few days before. The patient complained of a pricking sensation at the injured area while moving the neck. A contrasted computed tomography was performed for further evaluation of the needle toward the vascular network of the neck, showing a close location by the left facial artery, parallel to the styloid process of the temporal bone. The needle was then released from the underlying tissues and retrieved. Although considered a rare intercurrence, there are still reports of breaking needles during dental anesthesia. Such reports are almost always related to inferior alveolar nerve blocks, associated with the use of short, thin needles, and after multiple bending movements before the insertion of the needle in the tissues. Accurate image examinations such as contrasted computed tomography are of great importance for planning the surgical removal, especially in patients of migration next to important vessels of the neck.
Keywords: Anesthesia; Dental; Neck dissection; Tomography; Xray Compute